2019
DOI: 10.1002/elan.201900279
|View full text |Cite
|
Sign up to set email alerts
|

Batch Injection Analysis with Amperometric Detection for DNA Biosensing Applications

Abstract: In this work, batch injection analysis with the amperometric detection (BIA‐AD), employing a detection cell designed to adapt a screen‐printed carbon electrode (SPCE) was used for the first time as a robust electroanalytical system for DNA biosensing applications. The sensitive amperometric detection was used to evaluate the structural changes in double‐stranded DNA (dsDNA) after UV‐C irradiation of its solution for a given time. Batching of DNA samples was performed by precise electronic pipette microinjectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Concerning the pharmaceutical samples, it is mainly a matter of determining the active substance content (including the determination of their excipients) and also simultaneous determination of more than one drug in a sample [ 43 ]. BIA was also used in detecting DNA damage caused by UV radiation [ 44 ].…”
Section: Batch Injection Analysismentioning
confidence: 99%
“…Concerning the pharmaceutical samples, it is mainly a matter of determining the active substance content (including the determination of their excipients) and also simultaneous determination of more than one drug in a sample [ 43 ]. BIA was also used in detecting DNA damage caused by UV radiation [ 44 ].…”
Section: Batch Injection Analysismentioning
confidence: 99%
“…The attractive features of the BIASPE system were also explored for the on-site determination of carbendazim, catechol and hydroquinone in tap water, [20] metals (Zn 2 + , Cd 2 + , Pb 2 + , Cu 2 + , and Hg 2 + ) in biodiesel samples, [85] glucose in artificial serum sample, [21] antioxidant 2,6-di-tert-butylphenol (2, in biodiesel and jet-fuel using hydro-organic media as the supporting electrolyte, [26] lead in aviation fuel samples, [86] omeprazole in pharmaceutical samples, [87] corrosion inhibitors (2,5-dimercapto-1,3,5-thiadiazole) in fuel ethanol, seawater and mineral oil samples, [88] levamisole and sodium levothyroxine in pharmaceutical samples, [89] nitrite and uric acid in biological fluids (urine, plasma, saliva, and serum), [90] antioxidant capacity of edible oil samples, [91] benzocaine and tricaine in fish fillets, [92] and a robust electroanalytical system for detection of UVinduced DNA degradation. [93] Recently, Mendonça et al [94] reported a low-cost mechanized system fabricated using fused deposition modelling 3D-printing technology to perform injections on an electrochemical cell in wall-jet configuration (similar to a common BIA cell). Expanding the possibility for analysis with extremely small volumes (0.5 μL), the system also allows automatic handling of microliter aliquots (dilutions, mixtures, exactly time-controlled reactions), similar to FIA and SIA systems.…”
Section: -Nitro-p-phenylenediaminementioning
confidence: 99%
“…Batch‐injection analysis systems with electrochemical detection can be considered as a simple electrochemical and portable analytical system [22–25]. The operation of the system involves the injection of small volumes (10–150 μL) of samples (usually with an electronic micropipette) directly to the working electrode surface (wall‐jet configuration) in an electrochemical cell filled with supporting electrolyte [26, 27].…”
Section: Introductionmentioning
confidence: 99%